Life‐history evolution in response to changes in metapopulation structure in an arthropod herbivore. (4th January 2016) - De Roissart, Annelies; Wybouw, Nicky; Renault, David; Van Leeuwen, Thomas; Bonte, Dries
Summary: The persistence and dynamics of populations largely depend on the way they are configured and integrated into space and the ensuing eco‐evolutionary dynamics. We manipulated spatial and temporal variation in patch size in replicated experimental metapopulations of the herbivore mite Tetranychus urticae and followed evolutionary dynamics over approximately 30 generations. A significant divergence in life‐history traits, physiological endpoints and gene expression was recorded in the spatially and spatiotemporally variable metapopulation, but also a remarkable convergence relative to the stable reference metapopulation in traits related to size and fecundity and in its transcriptional regulation. The observed evolutionary dynamics are tightly linked to demographic changes, more specifically frequent episodes of resource shortage that increased the reproductive performance of mites on tomato, a challenging host plant. This points towards a general, adaptive stress response in stable spatial variable and spatiotemporal variable metapopulations that pre‐adapts a herbivore arthropod to novel environmental stressors. Abstract : Lay Summary